2011
DOI: 10.3945/jn.110.134387
|View full text |Cite
|
Sign up to set email alerts
|

20-Year Trends in Filipino Women's Weight Reflect Substantial Secular and Age Effects

Abstract: Increasing obesity in low- and middle-income countries is well documented in cross-sectional studies. However, few longitudinal studies identify factors that influence individual weight gain patterns over time in relation to the major social and economic changes that now characterize these settings. This study uses data from adult Filipino women participating in the Cebu Longitudinal Health and Nutrition Survey from 1983 to 2005. A sample of 3005 women contributed 1-8 observations each. Longitudinal mixed effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 29 publications
5
32
0
Order By: Relevance
“…In contrast, other studies have shown that individuals who initially had excess weight gained less weight over time than participants who were leaner at baseline . In CARDIA, aging‐related weight gain was greatest in the early to mid‐20s for most groups, which is consistent with other epidemiological studies in the U.S. and other countries that have demonstrated the greatest adult weight gains in early adulthood .…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, other studies have shown that individuals who initially had excess weight gained less weight over time than participants who were leaner at baseline . In CARDIA, aging‐related weight gain was greatest in the early to mid‐20s for most groups, which is consistent with other epidemiological studies in the U.S. and other countries that have demonstrated the greatest adult weight gains in early adulthood .…”
Section: Introductionsupporting
confidence: 85%
“…However, most of this previous research has examined weight gain over time periods ranging from 5 to 10 years , although two studies, including one in the U.S. and one in the Philippines , followed the same participants for 20 years. In the U.S. study, weight gain was most pronounced in early adulthood (aged 25–35 years), and this was consistent for men and women as well as Blacks and Whites .…”
Section: Introductionmentioning
confidence: 99%
“…It is a lower-middle income nation undergoing significant economic, dietary and lifestyle changes. Although rates of overweight/obesity, CVD, and metabolic syndrome are relatively low, they are on the rise (Adair et al 2011; Pedro et al 2007; Tanchoco et al 2003). At the same time, infectious disease accounts for more than 30% of all mortality in Southeast Asia, with pneumonia, diarrhea, and tuberculosis serving as major contributors (WHO 2004).…”
mentioning
confidence: 99%
“…Motivated by the increasing prevalence of obesity in the Philippines, 41, 42 and other lower-income countries, 7 particularly in urban areas, we aimed to identify spatial clusters of obesity in Metropolitan Cebu. By identifying spatial clusters and relating them to the urbanicity of the study area, we hoped to facilitate further etiological research aimed at identifying environmental determinants of obesity in this study area.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mothers of this birth cohort underwent a remarkable sixfold increase in OW and obesity prevalence between 1983 and 2005. 42 Space-time clustering of obesity in the cohort mothers will provide additional insights and help overcome these limitations.…”
Section: Discussionmentioning
confidence: 99%